Proses Rekrutmen Dan Seleksi Tenaga Kerja Pada PT Jamkrida Kalimantan Timur - Andi Syarifuddin; Armini Ningsih; Citra Nur Azizah; Wulan Nur Aisyiyah (Politeknik Negeri Samarinda, 2022)
This research is motivated by the importance of the employee recruitment and selection process. The purpose of this study was to determine the process of recruitment and selection of employees at PT. Jamkrida East Kalimantan. The data analysis method is carried out in the form of qualitative data analysis through data processing as a descriptive research process. Namely the data obtained is then analyzed and compared with theories and then evaluated and analyzed. The process of data analysis in this research is by analyzing the data, reducing the data, compiling the data, presenting the data, and checking the validity of the data. The results of the research obtained are the employee recruitment process carried out opening announcements through existing media and receiving applicants' files is still done manually. The selection system carried out uses a gradual selection method which has a weakness, one of which is that there is a time lag that is not explained in detail how long the stages are adjusted to the job description in order to produce good performance for the company. However, the promotion process for the old employees is not explained in detail on the provisions that form the basis for the promotion. It is recommended to make job vacancies announcements online via the internet in other words can be accessed directly on-line to be more efficient. The selection process is gradually carried out in a more structured, scheduled and efficient manner. Realizing the principle of the right person in the right job will be much easier if the recruitment and selection process produces a number of competent employees. Employee performance appraisal should be carried out thoroughly to all employees, both permanent employees and contract employees.